Major Salivary Gland Tumors: A Clinicopathological Study (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Major salivary gland tumors comprise a morphologically diverse group of rare tumors. The tumors also have variations in their clinicopathological profile related to racial and geographic differences. Objective: To find out the frequency of different types of major salivary gland neoplasm. Methodology: This cross sectional study was carried out on 50 patients having major salivary gland tumor in the departments of Otolaryngology of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and Sir Salimullah Medical College Hospital from January 2010 to September 2010. Result: In this study, most cases occur in 5th decade. Incidence of malignant and benign parotid neoplasm was found 23.8% and 76.2% respectively. Benign and malignant tumors of submandibular gland were 50% in each group. No sublingual gland neoplasm was found in this group. Conclusion: Parotid gland was the most common site of origin of both benign and malignant tumours. Plemorphic adenoma was the most common benign salivary gland tumour and mucoepidermoid carcinoma was the most frequent malignant neoplasm. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16250 J Shaheed Suhrawardy Med Coll, 2013;5(1):43-45